(untitled) (Rivista di Psicopatologia Forense, Medicina Legale, Criminologia, 2018)
Stalking is the product of an interaction between context (including the dyadic relationship between stalker and victim) and individual factors such as psychopathology. Those who have stalking behaviour are often affected by mental disorders that may have a direct or indirect role in committing stalking. Literature reports that stalkers of former partners represent the widest sub-category of stalkers. A 2003 study indicates an average percentage of 49% stalkers of former partners reported in 40, showing a significant diversity of stalking behaviours with a faster wearing out rate. Several studies indicate a greater prevalence of psychosis among those who persecute strangers or acquaintances compared to stalkers of former partners (25% vs 11%). Some studies, besides the present survey, indicate a high prevalence of not otherwise specified Personality Disorders in stalkers, suggesting that stalking behaviour may be associated with several personality traits of various disorders. This study aims at finding empirical evidence to the data reported by the relevant scientific literature. We examined the expert surveys of 20 stalkers subjected to psychiatric-forensic evaluation for the crime of stalking (article 612/bis) in the years 2016/2017, drawn up by the Forensic Psychiatry Service in Cagliari. Through a specific grid, which allowed to guarantee anonymity and that stalkers could not be identified, they analyzed some demographic variables (age, sex, marital status, educational qualification), stalkers" diagnoses, victims" typology, types of stalking performed, paying a particular attention to violence manifestations, stalking duration and some psychiatric-forensic data. Our survey has highlighted that 19 stalkers (95%) are males, do not have a stable affective relationship and had to refer at least once to the Mental Health Service; (70%) of stalkers are unemployed or retired. From the psychiatric-forensic point of view, 14 stalkers (70%) are partially mind defective, 5 (25%) are totally mind defective, 1 has been recognized as mentally incompetent; 13 (65%) are socially dangerous. Furthermore, 45% of stalkers are affected by not otherswise specified (NOS) Personality Disorder. The prevalent diagnoses (Axis I) detected are: 8 stalkers (40%), are affected by Substance Use Disorder, 6 (30%), Bipolar and related disorders, 5 (25%) Spectrum Disorders of Schizophrenia and other Psychotic Disorders; 45% of victims of stalking are former partners. Due to the high possibility that stalkers develop a violent behaviour, present in half of the stalkers of former partners, and the chance of crime recidivism, in particular among stalkers affected by Personality Disorder, the Service of Forensic Psychiatry in Cagliari, in agreement with the Court, is drawing up guidelines that provide for the establishment of proper services where to follow the stalkers in order to limit recidivism of this crime.